Chikungunya virus infection - Sam, I-C; AbuBakar, Sazaly (Malaysian Medical Association, 2006)
Chikungunya virus (CHIKV) is a mosquito-borne alphavirus which causes epidemic fever, rash and polyarthralgia in Africa and Asia. Two outbreaks have been reported in Malaysia, in Klang, Selangor (1998) and Bagan Panchor, Perak (2006). It is not known if the outbreaks were caused by the recent introduction of CHIKV, or if the virus was already circulating in Malaysia. Seroprevalence studies from the 1960s suggested previous disease activity in certain parts of the country. In Asia, CHIKV is thought to be transmitted by the same mosquitoes as dengue, Aedes aegypti and Ae. albopictus. Due to similarities in clinical presentation with dengue, limited awareness, and a lack of laboratory diagnostic capability, CHIKV is probably often underdiagnosed or misdiagnosed as dengue. Treatment is supportive. The prognosis is generally good, although some patients experience chronic arthritis. With no vaccine or antiviral available, prevention and control depends on surveillance, early identification of outbreaks, and vector control. CHIKV should be borne in mind in sporadic cases, and in patients epidemiologically linked to ongoing local or international outbreaks or endemic areas.